Analisis Timbulan, Komposisi dan Potensi Daur Ulang Sampah Kabupaten Mandailing Natal - Dewilda, Yommi; Aziz, Rizki; Hokiartha, Rendi; Rinaldi, Jon (Jurnal Serambi Engineering, 2025)
The level of waste management services in Mandailing Natal Regency is still low. Unserved communities manage their waste by burning it or dumping it into rivers. Mandailing Natal Regency does not yet have the data on solid waste generation and composition needed to formulate a waste management plan. This study aims to determine the amount of solid waste generation, composition and recycling potential in Mandailing Natal Regency. The sampling methodology is based on SNI 19-3964-1994. Domestic waste generation in weight units is 0.574 kg/person/day, while in volume units it is 2.357 litres/person/day. Non-domestic waste generation averages 0.289 kg/person/day in weight units and 2.616 litres/person/day in volume units. The composition of domestic waste is dominated by food waste with 41.33%, paper waste with 6.37%, plastic waste with 24.08%, textile waste with 2.59%, garden waste with 11.66%, metal with 4.64%, glass with 1.18% and other waste with 8.14%. The composition of non-domestic waste is as follows: food waste 38.69%, yard waste 9.14%, paper 14.04%, plastic 24.07%, textile 1.65%, glass 1.52%, metal 2.80% and other waste 8.09%. The components of domestic waste with recycling potential are food waste 82.75%, plastic 87.03%, paper 70.24%, glass 89.74% and metal 88.89%. The recycling potential of non-domestic waste is 78.78% for food waste, 90.36% for plastic waste, 75.36% for paper, 90.41% for glass and 76.06% for metal.